Individualization of microsurgical tactics during clipping cerebral arterial aneurysms - S.O. Lytvak (Ендоваскулярна нейрорентгенохірургія, 2018)
Objective — to determinate clinical and anatomical options of influence of strategy and tactics of microsurgical treatment cerebral arterial aneurysms (AA) to increase the effectiveness of clipping surgery.